Performance Analysis of Local Revenue Management Pariaman City from 2011-2017 - Indrawani, Sri Ayu (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2019)
This study aims to determine the development and analyze the performance of PAD management in Pariaman city, which is measured by regional financial analysis, namely looking at the level of revenue of PAD, PAD growth rate, PAD effectiveness ratio, PAD elasticity ratio, and Pariaman PAD tax ratio. This type of research is descriptive research using regional financial ratio analysis. The results of the study can be concluded that the development of regional original income in the city of Pariaman experienced fluctuations every year, even though the growth of the city of Pariaman was always positive, despite an increase and decrease every year. Viewed in terms of the effectiveness of regional revenue, the effectiveness rate is above 100%, although in 2016 and 2017 it produces values below 100 but can still be classified as very effective because they still range from 75-100. In addition, from the overall elasticity level it can be said to be less elastic because the results obtained are a small majority of 1, whereas if viewed from the perspective of the accepted local tax ratio, especially at regional revenue, the tax ratio is very good because of increasing annual returns and value above 100.